Opto-valleytronics in the 2D van der Waals heterostructure - Rasmita, Abdullah (2021)
The development of information processing device with minimum carbon emission is crucial in this information age. One of the approaches to tackle this challenge is by using valleys (local extremum points in the momentum space) to encode the information instead of charges. The valley information in some material such as monolayer transition metal dichalcogenide (TMD) can be controlled by using circularly polarized light. This opens a new field called opto-valleytronics. In this article, we first review the valley physics in monolayer TMD and 2D heterostructure composed of monolayer TMD and other materials. Such 2D heterostructure has been shown to exhibit interesting phenomena such as interlayer exciton, magnetic proximity effect, and spin-oTbit proximity effect, which is beneficial for opto-valleytronics application. We then review some of the optical valley control methods that have been used in the monolayer TMD and the 2D heterostructure. Finally, a summary and outlook of the 2D heterostructure opto-valleytronics are given.